Corrosion cracking propagation and fatigue strength of complex technical systems - A.R. Arutyunyan; R.A. Arutyunyan (Инженерно-строительный журнал, 2013)
The reliability problem of complex mechanical systems composed of some number of elements with the crack type defects, which growth rate is essentially governed by the processes of corrosion fatigue, was considered. Among these systems there are different engineering constructions: energetic, transport, chemical and others. Taking into account that the reliability of a system as a whole depends on the reliability of individual elements and the way of their connection, the systems with the elements connected parallel, in series and with reserved elements were considered. For each system the reliability function, based on the Poisson’s and Weibull’s distribution, was defined. The criteria for corrosion fatigue for each system were formulated and corresponding fatigue curves were constructed. In accordance with these results the practical suggestions how to design the most reliable systems were derived.